Analisis Perbandingan Kinerja Keuangan Bank Syariah Di Indonesia Menggunakan Perbandingan Income Statement Approach (ISA) dan Volume Added Reporting (VAR) (Studi Pada Bank Syariah di Indonesia Periode 2014-2018) - Risa Rossita; M. Agus Salim; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study discusses to discuss and analyze Comparison of Islamic Bank Financial Performance in Indonesia Using Comparison of Income Statement (ISA) and Volume Added Reporting (VAR). Population and sample are Islamic Commercial Banks registered with Bank Indonesia for the period 2014-2018. The data analysis this study used SPSS version 20. The sampling technique used in this study was purposive sampling method and the data testing technique used in this study was normality test, descriptive statistical test and research hypothesis testing. The results of this study indicate a significant difference in Islamic finance when viewed from the ROA ratio with the approval of ISA and VAR. Obtained from the significance of the performance of Islamic banking when seen from the ROE ratio to get ISA and VAR. Obtained from the significance of the performance of Islamic banking when viewed from the LBAP ratio to get ISA and VAR. Obtained from the significance of the performance of Islamic banking when seen from the ratio of NPM by obtaining ISA and VAR. There is no significant difference in the performance of Islamic banking when seen from the ratio of BOPO to ISA and VAR.            The results of this study indicate that: (1) there is a significant difference in the performance of Islamic banking when viewed from the ROA ratio with the ISA and VAR approach, (2) there is a significant difference in the performance of Islamic banking when seen from the ROE ratio with the ISA and VAR approach, (3) there is a significant difference in the performance of Islamic banking when viewed from the LBAP ratio with the ISA and VAR approach, (4) there is a significant difference in the performance of Islamic banking when seen from the ratio of NPM with the ISA and VAR approach, (5) there is no difference which is significant in the performance of Islamic banking when seen from the ratio of BOPO with the ISA and VAR approaches.Keywords: Income Statement Approach, Volume Added Reporting, Financial Performance